Upaya Peningkatan Kesadaran Masyarakat Kabupaten Pandeglang Dalam Pencegahan Penyakit Diabetes Dan Tuberculosis - Yusransyah Yusransyah; Sofi Nurmay Stiani; Renditya Ismiyati; Sylvianti Maharani; Sumarlin US; Eneng Elda Ernawati (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Diabetes mellitus and tuberculosis are one of the diseases that are of serious concern to the government. Diabetes is caused by excessive consumption of sugar in the body. Tuberculosis is caused by bacteria that enter the body. Both diseases can be cured with a healthy lifestyle and taking the medication regularly. Community service activities can be a means of education and attract public interest in diabetes and tuberculosis. Community service is carried out by providing education and conducting health checks so that people can apply a healthy lifestyle and increase awareness of maintaining health.